2019
DOI: 10.4103/jcvjs.jcvjs_115_18
|View full text |Cite
|
Sign up to set email alerts
|

Treatment algorithm for spontaneous spinal infections: A review of the literature

Abstract: Background: Primary spinal infections are rare pathologies with an estimated incidence of 5% of all osteomyelitis. The diagnosis can be challenging and this might result in a late identification. The etiological diagnosis is the primary concern to determine the most appropriate treatment. The aim of this review article was to identify the importance of a methodological attitude toward accurate and prompt diagnosis using an algorithm to aid on spinal infection management. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…This case demonstrates that low-dose celecoxib may effectively treat pain in patients with VO. Literature exploring the management of VO has focused on antibiotics, immobilization and surgical indications [ 3 ]. Even with more aggressive antibiotic regimens, back pain often persists for weeks to months due to gradual resolution of the infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This case demonstrates that low-dose celecoxib may effectively treat pain in patients with VO. Literature exploring the management of VO has focused on antibiotics, immobilization and surgical indications [ 3 ]. Even with more aggressive antibiotic regimens, back pain often persists for weeks to months due to gradual resolution of the infection [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to constitute between 3% and 5% of all osteomyelitis cases and most frequently occurs in the lumbar spine [ 1 , 2 ]. Infection most commonly spreads to the spine via hematogenous dissemination, but direct inoculation from trauma or surgery and contiguous spread from adjacent tissues are also possible [ 3 ]. Risk factors include diabetes mellitus, renal failure, liver cirrhosis, autoimmune diseases, history of substance abuse and previous spinal surgeries [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that a daptomycin-containing regimen was strongly associated with clinical cure. Considering that over 70% of VO etiology is caused by Gram-positive strains but etiology of infection is obtained in about 75% of cases, these data may help physicians to choose the appropriate antibiotic regimen, especially in patients without a confirmed etiology of infection, in order to early evaluate also the criteria to switch to oral therapy [ 7 , 35 ]. However, randomized clinical trials are mandatory to confirm or to exclude these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Infections of the musculoskeletal system are difficult to treat and frequently require a protracted and rigorous therapy [ 1 ]. Spinal infections, or spondylodiscitis, in particular represent a therapeutic challenge [ 2 , 3 ] The intervertebral disc space is primarily difficult to access antibiotically, so bacteria might persist here and can be reactivated when the immune system is weakened [ 4 ].…”
Section: Introductionmentioning
confidence: 99%